2022
DOI: 10.1002/jssc.202200374
|View full text |Cite
|
Sign up to set email alerts
|

Screening of potent α‐glucosidase inhibitory and antioxidant polyphenols in Prunella vulgaris L. by bioreaction–HPLC–quadrupole‐time‐of‐flight‐MS/MS and in silico analysis

Abstract: Prunella vulgaris L. is a well-known traditional Chinese medicine for blood glucose homeostasis and antioxidant potential. Ethyl acetate fraction of P. vulgaris L. demonstrated higher phenolic content (85.53 ± 6.74 mg gallic acid equivalents per gram dry weight), α-glucosidase inhibitory (IC 50 , 69.13 ± 2.86 μg/ml), and antioxidant (IC 50 , 8.68 ± 1.01 μg/ml) activities. However, the bioactive polyphenols responsible for the beneficial properties remain unclear.Here, bioreaction-HPLC-quadrupole-time-of-flight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
(66 reference statements)
1
9
0
Order By: Relevance
“…This difference may be associated with the growing conditions of P. vulgaris . The observed TPC values of P. vulgaris are consistent with those of previous findings (Cheng et al, 2022), showing that the ethyl acetate fraction of P. vulgaris had the highest TPC (85.53 ± 6.74 mg GAE/g DW).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This difference may be associated with the growing conditions of P. vulgaris . The observed TPC values of P. vulgaris are consistent with those of previous findings (Cheng et al, 2022), showing that the ethyl acetate fraction of P. vulgaris had the highest TPC (85.53 ± 6.74 mg GAE/g DW).…”
Section: Resultssupporting
confidence: 92%
“…The flavonoids present in P. vulgaris are thus able to inhibit α ‐glucosidase activity. However, studies have reported α ‐glucosidase inhibition by caffeic acid in P. vulgaris , shown by molecular docking and bioreaction ultrafiltration, as well as in alloxan‐induced diabetic mice (Cheng et al, 2022; Raafat et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The FMO theory subdivided the electron distributed around the kaempferol molecule into molecular orbitals with different energy levels, among which the HOMO ( E HOMO = −5.7579 eV) and LUMO ( E LUMO = −1.8939 eV) were mainly studied (Figure 4). The energy gap was 3.8640 eV, indicating the reaction may occur to some extent [42–44]. The small E gap was more favorable for the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Huber et al evaluated the molecular interactions between NADES and the sample by combining COSMO-RS and NMR experiments. 1 H NMR and NOESY spectra further showed that nonspecific and targeted intermolecular interactions were the driving force for the effective solubility enhancement of curcumin [99] the extraction is mainly contributed by hydrophobic interactions. The possible extraction mechanism of TRDES by density functional theory (DFT) calculation was proposed [84].…”
Section: The Combination Of Computer Simulations and Experimentsmentioning
confidence: 95%
“…Bioactive compounds are physiologically active components that have regulatory functions such as antibacterial, antioxidant, anti-inflammatory, and anti-cancer activity [1][2][3]. Some extraction and separation techniques, such as liquid-liquid extraction, supercritical fluid extraction, Soxhlet extraction, reflux, steam distillation, percolation, and precipitation separation, are used in extraction and separation processes [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%